Everything you need to know to survive teaching - Ranting Teacher (New York, NY : Continuum International Pub. Group, 2007)
In this collection of the nation's favourite 38 teaching rants, the Ranting Teacher finds solutions to the issues that really bother teachers - from controlling behaviour, wising up to kids' excuses and coping with extracurricular activities, to dealing with parents, curing hangovers and impressing the inspectors." "This book is the ultimate survival guide for teachers everywhere."--Jacket.
Keywords: Teaching -- Great Britain; Teachers -- Professional relationships -- Great Britain